Hızlandırılmış rehabilitasyon programının çift tünel ön çapraz bağ tamiri yapılan sporcular üzerine etkisi - Kaptan, Hüseyin Ali (My University, 2010)
1.ÖZET Çalışmanın amacı, hızlandırılmış rehabilitasyon programının, çift tünel (ÇT) ön çapraz bağ (ÖÇB) rekonstrüksüyonu yapılan hastalardaki etkinliğini, tek tünel (TT) rekonstrüksüyonlu hastalarla karşılaştırarak araştırmaktır. Çalışmaya, ÇT ve TT hamstring otogrefti ile rekonstrüksüyon yapılmış ve hızlandırılmış rehabilitasyon programına katılmış 40 hasta alınmıştır. Olgular 6 hafta süreyle haftada 3 gün ve 2 hafta süreyle haftada 2 gün rehabilitasyon programına alınmış, takip eden 4 hafta boyunca haftada 1 gün ev zlenmiş, TT ve ÇT ÖÇB rekonstrüksüyonu olmak üzere basit eşleştirme yöntemiyle 2 gruba ayrılmıştır. Hastaların günlük yaşam aktivitelerine, iş ve spor hayatlarına ve eski performansa dönüşleri araştırılmıştır. Bu amaçla Görsel Analog Skala (VAS), Lsyholm, Tegner ve IKCD formları kullanılmıştır. Eklem hareket açıklıkları (NEH), diz çevresi ölçümleri, zıplama testleri ve kuvvet yönünden izokinetik testler yapılmıştır. Lsyholm, Tegner, VAS, IKCD değerlendirme ölçümleri, sağlam ve hasta tarafın NEH ve çevre ölçümleri, zıplama testleri ve izokinetik testlerde gruplar arasında istatistiksel olarak anlamlı bir farklılık bulunmamıştır (p>0.05). Hasta ve sağlam dizler arasında grup içinde yapılan değerlendirmelerde; ÇT ve TT gruplarında, NEH, patella üstü 10cm- 20 cm ortalamaları arasında anlamlı bir faklılık izlenmiştir (p<0.05 ve p<0.001). 6m sıçrama zamanı değerlendirildiğinde her iki grupta hasta ve sağlam eklemlerin karşılaştırılması istatistiksel olarak anlamlı bulunurken (p<0.05), tek adım atlamada sadece ÇT grubunda istatistiksel olarak anlamlılık bulunmuştur (p<0.05). Hızlandırılmış rehabilitasyon spora ve günlük yaşam seviyelerine dönüşü kolaylaştırması, brace, koltuk değneği gibi yardımcı cihazlara bağımlılığı azaltması ve hastanın rehabilitasyon programına intibakını kolaylaştırlması açısından avantajlı bir programdır. Spor yaralanmaları, diz eklemi, ön çapraz bağ, rehabilitasyon, çift tünel tamir 2.

The Effect of Accelerated Rehabilitation Program on Double Bundle Anteior Curicuate Ligament Reconstructed Athletes The purpose of this study is to exhibit the efficiency of the accelerated rehabilitation program on double tunnel (DT) anterior cruciate ligament (ACL) reconstructed knees comparing to the single tunnel (ST) reconstructed ones. 40 patients, undergone ACL reconstruction surgery with DT and ST hamstring autograft techniques and attended to the accelerated rehabilitation program were included in the study. All of the subjects attended to the rehabilitation program as 3days/ week for 6 weeks and 2 days/ week for 2 weeks and for the following 4 weeks followed with one day home program. Patients were divided into two grups by siple matching technique as ST and DT ACL reconstructed. Returning to daily activities, business and sports activities and the performance before the injury of all the patients were noted. For this purpose we used Visual Analog Scale (VAS), Lsyholm, Tegner ve IKDC forms. Range of Motion (ROM), knee circumference measurements, hopping tests, izokinetic tests due to strength measurement were performed. There were no significant difference between the Lsyholm, Tegner, VAS, IKDC evaluation scores, ROM and circumference measurements of the normal and the injured knee, hopping tests and isokinetic tests regarding both of the groups. (p>0.05). When the normal and injured knee were evaluated individually; there were singnificant differences between the mean values of ROM and suprapatellar 10cm-20cm thigh circumference differences in the DT and ST groups. (p<0.05 and p<0.001). When 6m hopping time and both knees of both groups compared, ST ACL reconstructed knees were significantly normal as the uninjured knee.(p<0.05) In single step hopping test when both knees were evaluated individually in the DT group, DT ACL reconstructed knees were significantly normal as the uninjured knee.(p<0.05) As a conclusion The accelerated rehabilitation program is superior for facilitating the return to sports and normal daily activities, and patient cooperation to the rehabilitation program and decreasing the dependence to the ambulatory assisting devices like braces and crutches. Key Words: Sports injuries, knee joint, Anterior cruciate ligament, Rehabilitation, Double tunnel reconstruction . 2. SUMMARY The Effect of Accelerated Rehabilitation Program on Double Bundle Anteior Curicuate Ligament Reconstructed Athletes The purpose of this study is to exhibit the efficiency of the accelerated rehabilitation program on double tunnel (DT) anterior cruciate ligament (ACL) reconstructed knees comparing to the single tunnel (ST) reconstructed ones. 40 patients, undergone ACL reconstruction surgery with DT and ST hamstring autograft techniques and attended to the accelerated rehabilitation program were included in the study. All of the subjects attended to the rehabilitation program as 3days/ week for 6 weeks and 2 days/ week for 2 weeks and for the following 4 weeks followed with one day home program. Patients were divided into two grups by siple matching technique as ST and DT ACL reconstructed. Returning to daily activities, business and sports activities and the performance before the injury of all the patients were noted. For this purpose we used Visual Analog Scale (VAS), Lsyholm, Tegner ve IKDC forms. Range of Motion (ROM), knee circumference measurements, hopping tests, izokinetic tests due to strength measurement were performed. There were no significant difference between the Lsyholm, Tegner, VAS, IKDC evaluation scores, ROM and circumference measurements of the normal and the injured knee, hopping tests and isokinetic tests regarding both of the groups. (p>0.05). When the normal and injured knee were evaluated individually; there were singnificant differences between the mean values of ROM and suprapatellar 10cm-20cm thigh circumference differences in the DT and ST groups. (p<0.05 and p<0.001). When 6m hopping time and both knees of both groups compared, ST ACL reconstructed knees were significantly normal as the uninjured knee.(p<0.05) In single step hopping test when both knees were evaluated individually in the DT group, DT ACL reconstructed knees were significantly normal as the uninjured knee.(p<0.05) As a conclusion The accelerated rehabilitation program is superior for facilitating the return to sports and normal daily activities, and patient cooperation to the rehabilitation program and decreasing the dependence to the ambulatory assisting devices like braces and crutches. Key Words: Sports injuries, knee joint, Anterior cruciate ligament, Rehabilitation, Double tunnel reconstruction .
Keywords: Fizik Tedavi; Rehabilitasyon